(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Sometimes in life there are such mind-boggling renewals and changes that these historical processes are recognized as periods of great creativity.It’s no secret that today human interests have risen to the highest level of value in the Republic of Uzbekistan, and a completely new system is being introduced in the process of working with citizens’ appeals in the activities of all state agencies. As a result, beautification and construction works are being carried out.